2013
DOI: 10.4269/ajtmh.13-0170
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Disease Severity in Patients Admitted to a Cholera Treatment Center in Urban Haiti

Abstract: Cholera, previously unrecognized in Haiti, spread through the country in the fall of 2010. An analysis was performed to understand the epidemiological characteristics, clinical management, and risk factors for disease severity in a population seen at the GHESKIO Cholera Treatment Center in Port-au-Prince. A comprehensive review of the medical records of patients admitted during the period of October 28, 2010–July 10, 2011 was conducted. Disease severity on admission was directly correlated with older age, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Findings from this study also support those of Valcin [13] who found out that the leading age group is adults (21 -40 ) years of age, whereas children who were less than or equals to ≤ 20 years of age had a high percentage of diarrhea perhaps because of rotavirus or other childhood diarrheal illness in addition to bacterial infections.…”
Section: Socio-demographic and Socioeconomic Factorssupporting
confidence: 89%
“…Findings from this study also support those of Valcin [13] who found out that the leading age group is adults (21 -40 ) years of age, whereas children who were less than or equals to ≤ 20 years of age had a high percentage of diarrhea perhaps because of rotavirus or other childhood diarrheal illness in addition to bacterial infections.…”
Section: Socio-demographic and Socioeconomic Factorssupporting
confidence: 89%
“…5 Seasonal peaks followed the rainy season associated with flooding and surface water contamination. 6,7 Lack of sanitation and access to potable water are responsible for continued cholera outbreaks around the world. In 2012, the WHO estimated that 1.4 billion were at risk for cholera and that every year cholera accounts for 28,000-142,000 deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] An alternative explanation is that children less than five years of age with diarrhea were less likely to have cholera because this was a newly introduced epidemic to which the whole population is immunologically naive. 30 Of note, 39.5% of the specimens from the CTC and 29.0% of those from the ORP had no pathogens detected by the xTAG GPP PCR, although 14.3% of the CTC cases and 18.4% of the ORP cases were culture positive for V. cholerae. The cases that were negative by the xTAG GPP PCR and V. cholerae culture could have been caused by pathogens not included in the xTAG GPP PCR panel and/or to emerging or yet unrecognized causes of diarrhea in Haiti.…”
Section: Discussionmentioning
confidence: 99%